The 2019 Novel Coronavirus (2019-nCoV): Novel Virus, Old Challenges - Duarte, R (2020)
In late December 2019, global attention shifted to China after several local health facilities reported clusters of patients with pneumonia of unknown origin epidemiologically linked to the Huanan Seafood Wholesale Market in the municipality of Wuhan, one of the country’s central cities. Local health authorities identified a novel betacoronavirus, provisionally called 2019-nCoV, the third zoonotic coronavirus in three decades to cross species infecting humans and raising global health concerns. Chinese government took extraordinary measures, to control the outbreak by closing The Market and by imposing a lockdown, first in Wuhan and later in twelve other Chinese cities. However, by the end of January 2020, there were 9826 confirmed cases (98.9% in China) a number that is estimated to be much higher and that is increasing every hour. The disease has now spread worldwide, with cases confirmed in 23 countries other than China, mainly in Southeast Asia but also in the United States of America and several European countries. On the 30 th of January, the World Health Organization’s Emergency Committee agreed that the outbreak now meets the criteria for a Public Health Emergency of International Concern. We are seeing the evolution of what is developing into a serious outbreak.